Photoepilation with high power LED - holonyak: evaluation of efficacy, satisfaction and incidence of side-effects - Bueno, Felícia Cadenas de Paiva; Afonso, João Pedro Ribeiro; Marques, Ricardo Henrique; Gomes, Danny Cristina Caixeta; Oguri, Mayara; Martins, Patrícia Sardinha Leonardo Lopes; Lopes-Martins, Rodrigo Alvaro Brandão (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Devices that use light, especially lasers, have become popular and are commonly used in aesthetics and hair removal. Laser-assisted photo epilation was originally described in 1996 and the proposed mechanism is based on the destruction of the follicular unit. Diode laser has been demonstrated to be an effective method for hair removal, however, the safety of patients with different skin types and colours is questionable due to thermal damage as the main side-effect. In this sense, the technological innovation of Photoepilation using high power LED equipment with high head cooling efficiency represents a great advance for the area. In this work, we evaluated the results of photoepilation using high-power LED in 117 patients with phototypes 01 to 06. Methods: A High potency LED equipment (Holoniak® – Adoxy Equipments – Brazil) was used. The LED allows the therapist to customize illumination parameters according to the sensitivity of the patients. All 117 participants were submitted to an initial sensitivity test to the LED irradiation, in order to determine adequate parameters to each participant. Sensitivity test was performed in both stationary and scanning modes. In scanning mode the test started with the following parameters – temperature of the at 10oC, fluence of 5 J/Cm2 and frequency 2 – 3 Hz. In stationary mode the sensitivity test started with temperature of the probe at 10 oC, fluence of 10 J/Cm2 and frequency of 0.8 Hz. No phototype restrictions were applied. To analyze the satisfaction of results, we created an arbitrary scale ranging from 1 to 4, where Grade 1 was considered unsatisfactory, Grade 2 - little satisfactory, Grade 3 - satisfactory and Grade 4 - very satisfactory. We also analyzed the number of sessions needed to achieve the hair removal result for each skin phototype. Results: Analyzing the percentage of satisfaction after LED photoepilation, satisfaction grade 3 and 4 represent approximately 95% of the participants. Surprisingly, there was no statistical correlation between the increase in skin phototype and the number of sessions needed to achieve the complete photoepilation effect. Unlike laser technology, which usually requires a high number of sessions for higher phototypes. No correlation with age was also reported. Conclusion: We can conclude that high power LED technology with effective tip cooling was able to achieve highly efficient results for 95.7% of treated patients, without the need to increase the number of sessions for phototypes 4 to 6.